Study of Injection Molding Warpage Using Analytic Hierarchy Process and Taguchi Method - Chen, Dyi-Cheng; Huang, Chen-Kun (Advances in Technology Innovation, 2016)
This study integrated Analytic Hierarchy Process and Taguchi method to investigate into injection molding warpage. The warpage important factor will be elected by Analytic Hierarchy Process (AHP), the AHP hierarchy analysis factor from documents collected and aggregate out data, then through the expert questionnaire delete low weight factor. Finally, we used Taguchi quality engineering method to decide injection molding optimized combination factors. Furthermore, the paper used injection pressure, holding pressure, holding time, mold temperature to analyze four factors, three levels Taguchi design data. Moreover, the paper discussed the reaction of each factor on the S / N ratio and analysis of variance to obtain the best combination of minimal warpage.